Optimization and formulation of fucoxanthin-loaded microsphere (F-LM) using response surface methodology (RSM) and analysis of its fucoxanthin release profile - Jaswir I.; Noviendri D.; Taher M.; Mohamed F.; Octavianti F.; Lestari W.; Mukti A.G.; Nirwandar S.; Hamad Almansori B.B. (MDPI AG, 2024)
Indexed by WOS/Scopus/ERA